2016
DOI: 10.1093/cercor/bhw306
|View full text |Cite
|
Sign up to set email alerts
|

Complex Trajectories of Brain Development in the Healthy Human Fetus

Abstract: This study characterizes global and hemispheric brain growth in healthy human fetuses during the second half of pregnancy using three-dimensional MRI techniques. We studied 166 healthy fetuses that underwent MRI between 18 and 39 completed weeks gestation. We created three-dimensional high-resolution reconstructions of the brain and calculated volumes for left and right cortical gray matter (CGM), fetal white matter (FWM), deep subcortical structures (DSS), and the cerebellum. We calculated the rate of growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 76 publications
5
110
0
2
Order By: Relevance
“…Possible reasons for these brain asymmetries are still debated, but various cognitive 40 disorders can involve deviations from typical asymmetry patterns, suggesting that laterality is an 41 important aspect of optimal brain development 11-13 . 42 Anatomical laterality of various brain structures becomes apparent in utero [14][15][16][17][18][19] , with the earliest 43 observation at just 11 post conception weeks (pcw), concerning the choroid plexuses (left larger than 44 right on average 14 ). In addition, lateralized arm movements have been observed as early as 8 pcw 20,21 .…”
Section: Introduction 37mentioning
confidence: 99%
“…Possible reasons for these brain asymmetries are still debated, but various cognitive 40 disorders can involve deviations from typical asymmetry patterns, suggesting that laterality is an 41 important aspect of optimal brain development 11-13 . 42 Anatomical laterality of various brain structures becomes apparent in utero [14][15][16][17][18][19] , with the earliest 43 observation at just 11 post conception weeks (pcw), concerning the choroid plexuses (left larger than 44 right on average 14 ). In addition, lateralized arm movements have been observed as early as 8 pcw 20,21 .…”
Section: Introduction 37mentioning
confidence: 99%
“…Furthermore, the JAK2 gene was found to have the highest expression level in the CBC, playing a central role in cognitive and emotional processing, which are key deficits in autism and other neuropsychiatric disorders (Menashe et al 2013;Wang et al 2014). The degrees of variation in expression levels in different brain regions are similar for MAPK7, and the peak expression levels of this gene appear in the mid-embryo phase, which involves a rapid increase in the volume of the cortical plate and the surface of the human brain (Clouchoux et al 2012;Andescavage et al 2017). The changes in cortical thickness, especially the volume gain of the gray matter during brain development associated with language development, social cognition, and behavioral control, are driven by a lack of typical age-related increase in cortical thickness and play an important role in early childhood autism (Smith et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is corroborated by recent reports of rapid fetal cortical GM growth in the third trimester compared with WM (28), as well as evidence of marked increases in fetal cortical GM growth alongside decreases in fetal WM and cerebellar growth during the third trimester (28–39 weeks) compared with the second trimester (18–27 weeks). (1) In their study, Andescavage and colleagues demonstrated fetal WM as the primary initial contributor to cerebral development peaking between 29 and 30 weeks’ gestation, at which point relative cortical GM volume begins to rapidly increase. (1) For infants born VPT, this period of accelerated growth taking place ex-utero is susceptible to disruption by exposures and stressors in the NICU, (2, 29) and our previous work suggests that regions of rapid cortical expansion are likely to be more sensitive to postnatal experience and insult.…”
Section: Discussionmentioning
confidence: 99%
“…(1) In their study, Andescavage and colleagues demonstrated fetal WM as the primary initial contributor to cerebral development peaking between 29 and 30 weeks’ gestation, at which point relative cortical GM volume begins to rapidly increase. (1) For infants born VPT, this period of accelerated growth taking place ex-utero is susceptible to disruption by exposures and stressors in the NICU, (2, 29) and our previous work suggests that regions of rapid cortical expansion are likely to be more sensitive to postnatal experience and insult. (30) Importantly, disruptions to normal cortical maturational trajectories during the late third trimester have been postulated to underpin the neurodevelopmental impairments seen in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation